2007
DOI: 10.1002/elan.200703873
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Stripping Voltammetry Using a Vibrating Electrode

Abstract: This work proposes a vibrating microwire electrode as working electrode in stripping voltammetry. The vibration was found to maintain a constant and thin (1 -2 mm) diffusion layer during the deposition step. The electrode vibration eliminated the need for external stirring of the solution, thus facilitating in situ detection in the environment. The vibration was effected by fixing a low-voltage (3 V), asymmetric, electrical rotor to the working electrode (a gold microwire of either 5 or 25 mm). The sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…An initially excellent performance of Au microwire with LOD of 6 and 25 pM for Hg and Cu in model solutions [32] was further improved by using it as a vibrating Au microwire electrode (VGME) [33]. Microwire electrodes of different sizes (5, 10 or 25 µm) were used for determination of traces of Zn, Cd, Pb, Cu, Hg, As, Sb in various environmental samples [19,[34][35][36][37].…”
Section: Progress Was Achieved In Liverpool Electrochemistry Group Bmentioning
confidence: 99%
“…An initially excellent performance of Au microwire with LOD of 6 and 25 pM for Hg and Cu in model solutions [32] was further improved by using it as a vibrating Au microwire electrode (VGME) [33]. Microwire electrodes of different sizes (5, 10 or 25 µm) were used for determination of traces of Zn, Cd, Pb, Cu, Hg, As, Sb in various environmental samples [19,[34][35][36][37].…”
Section: Progress Was Achieved In Liverpool Electrochemistry Group Bmentioning
confidence: 99%
“…Previous work using microwire electrodes found that the sensitivity was much improved by using electrode vibration instead of stirring of the solution [17,18]. This electrode was made by fitting a vibrating motor in the polypropylene pipette tip used for the Bi electrode ( Figure 1).…”
Section: Diffusion Layer Thickness Of the Stationary And Vibrating Bimentioning
confidence: 99%
“…(iii) By double concentration [71], reinforced mass transfer [72][73][74] or rapid voltage scanning [28,29,75].…”
Section: As(iii) Determination By Anodic Stripping Voltammetry (Asv)mentioning
confidence: 99%